Tiedustelusta sanottua - Sisällönanalyysi Eduskunnan lähetekeskusteluista - Välivaara, Ville (2025)
Finnish intelligence underwent a significant transformation on June 1, 2019, with the introduction of the so-called intelligence laws, which greatly expanded the jurisdictions of Finnish intelligence authorities. Concurrently, oversight of these authorities was also strengthened. This transformation highlights the importance of examining the role of intelligence in contemporary Finnish society. Intelligence has been studied within the relatively young field of intelligence studies. In recent years, however, there has been increasing recognition of the need to consider intelligence in a broader societal context, including cultural factors. This approach, known as the study of intelligence culture, is gaining attention within the field. Additionally, the ethical dimensions of intelligence work have become an important subject of discussion among both scholars and members of the intelligence community. The Finnish intelligence system and related legislation were thoroughly debated in two plenary sessions of the Finnish Parliament: one prior to the enactment of the intelligence laws in 2018, and another in 2022, two and a half years after their implementation. The purpose of this Master's thesis is to analyse the views expressed by Members of Parliament in these sessions to gain insight into their perspectives on intelligence, intelligence culture, and its ethics. This qualitative study employs theory-driven content analysis. The study concludes that intelligence in Finland is conducted in strict accordance with laws and regulations, with respect for human rights. Furthermore, effective and credible oversight is essential. Intelligence is expected to prevent security threats while providing crucial information for decision-making, establishing itself as a key component of Finnish society and enhancing national security.